Pengaruh Good Corporate Governance (GCG) terhadap Nilai Perusahaan pada Perusahaan Manufaktur di Bursa Efek Indonesia - Jeremia Sitorus; Jadongan Sijabat; Manatap Berliana Lumban Gaol (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the influence of Good Corporate Governance (GCG) on firm value among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. In this study, Good Corporate Governance is proxied by the audit committee, independent commissioners, and managerial ownership, while firm value is measured using Tobin's Q. The study employs a quantitative approach using secondary data obtained from the annual financial reports of food and beverage sub-sector manufacturing companies listed on the IDX. The sample was selected using a purposive sampling technique, resulting in 31 companies and a total of 93 observations over the three-year period. Multiple linear regression analysis, facilitated by the SPSS program, was used as the analytical method. The results indicate that, individually, the audit committee has a positive and significant effect on firm value, whereas independent commissioners and managerial ownership have a negative and significant effect on firm value. The coefficient of determination (Adjusted R-Square) of 0.283 indicates that 28.3% of the variation in firm value can be explained by the audit committee, independent commissioners, and managerial ownership, while the remaining 71.7% is influenced by factors outside the research model. These findings demonstrate that Good Corporate Governance mechanisms play a role in influencing firm value; therefore, companies need to enhance the effectiveness of their corporate governance implementation to boost investor confidence and firm value.